Comparative Adult Education and Learning Authors and Texts - Slowey, Maria (Studies on Adult Learning and Education, 2016)
This volume explores the topics of adult learning and education through the specific lens of comparative research. The book is divided into four chapters comprising two parts: an analytic essay followed by an anthology of readings from a selection of key texts intended to illustrate different perspectives, theories and/or approaches from varying perspectives in different countries. The book represents the second of a series dedicated to adult learning and education and developed within the ESRALE European project. Its companion books are: Empirical Research Methodology in Adult Learning and Education. Authors and Texts and Researches in Adult Learning and Education: the European dimension.